2021
DOI: 10.1007/s40519-021-01290-6
|View full text |Cite
|
Sign up to set email alerts
|

DRD2 and BDNF polymorphisms are associated with binge eating disorder in patients with weight regain after bariatric surgery

Abstract: Aim: To analyze the association and susceptibility of Single Nucleotide Polymorphisms (SNPs) in the DRD2 and BDNF genes with BED in patients with weight regain in the postoperative period of bariatric surgery. Methods: 177 individuals who underwent bariatric surgery with weight regain were evaluated and divided into two groups according to the BED diagnostic. The individuals were submitted to an anthropometric evaluation, analysis of the presence of BED using a validated questionnaire, and blood collection for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…In addition, it was also observed that the group with BED preoperatively had a higher mean score in the assessment of anxiety symptoms using the Beck Anxiety Inventory (BAI) than the group without BED and a higher frequency of moderate (23.0%) and severe (14.8%) anxiety. These results corroborate the literature, since studies showed that individuals with obesity and BED have higher rates of depression and anxiety than individuals with obesity and without BED [7,29,30]. Furthermore, these results suggested that patients with BED before surgery presented a series of factors that should be considered as risk factors after bariatric surgery, such as weight regain, psychiatric disorders, and the development of post-surgical complications [24,28].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, it was also observed that the group with BED preoperatively had a higher mean score in the assessment of anxiety symptoms using the Beck Anxiety Inventory (BAI) than the group without BED and a higher frequency of moderate (23.0%) and severe (14.8%) anxiety. These results corroborate the literature, since studies showed that individuals with obesity and BED have higher rates of depression and anxiety than individuals with obesity and without BED [7,29,30]. Furthermore, these results suggested that patients with BED before surgery presented a series of factors that should be considered as risk factors after bariatric surgery, such as weight regain, psychiatric disorders, and the development of post-surgical complications [24,28].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that patients with obesity and BED had higher levels of depression and anxiety in the preoperative period of bariatric surgery and increased weight and BMI in the late postoperative period of bariatric surgery. The literature suggests that in pre-bariatric surgery patients, the prevalence of BED may vary between 6 and 69% [7,10]. Our finding of a 51.7% BED prevalence was closer to the upper end of this spectrum.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…RDS manifests as an individual’s neurochemical deficiency at perceiving reward, including DA function deficiency and alterations in reward pathways, resulting in the seeking behavior of alternative ways to promote DA release, such as substance abuse and overeating [ 65 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], binge eating, etc. [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. Individuals, for example, carrying the DRD2 Taq1 A1 have a predisposition for reward-seeking behaviors due to DA function deficiency and alterations in reward pathways [ 65 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Genetic Factors Of Nicotine Use and Obesity Riskmentioning
confidence: 99%